The impact of bronchoalveolar lavage fluid metagenomics next-generation sequencing on the diagnosis and management of patients with suspected pulmonary infection - Zhou, Mei; Sun, Shengwen; Chen, Long; Xu, Huan; Liu, Lanlan; Lv, Jiaxi; Zhang, Jianchu; Xiong, Xianzhi (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesThis study aimed to enhance the comprehension of the practical utility of bronchoalveolar lavage fluid (BALF) metagenomic next-generation sequencing (mNGS) in the clinical management of patients with suspected pneumonia.MethodsWe retrospectively analyzed 296 individuals who underwent BALF mNGS and conventional microbial tests (CMTs) for suspected pneumonia. We compared the clinical characteristics between patients with pulmonary infection (PI) and those without pulmonary infection (NPI). The detection rate of mNGS and CMTs in different groups of patients were compared. The Sankey diagram was used to present the results of the influence of mNGS on diagnosis and treatment.ResultsComparison between PI and NPI showed that individuals with fever, concurrent malignant tumors, consolidation or ground-glass opacity on chest CT(Computed tomography) images, and elevated inflammatory markers on blood tests were more likely to develop lung infections. Analysis of the rate of positive detection between CMTs and mNGS in various subgroups revealed that mNGS had a significantly higher positive detection rate in patients with pulmonary infections (87.95% vs. 71.06%, p<0.001), in immunocompetent patients (86.91% vs. 68.08%, p<0.001), and in patients with malignant tumors (92.31% vs. 69.23%, p=0.035). Furthermore, mNGS helped initiate appropriate antibiotic treatment and confirmed the effectiveness of empirical treatment. Compared to immunocompetent patients, BALF mNGS in immunocompromised individuals with suspected lung infections yielded higher rates of accurate diagnosis (62.86% vs. 42.79%, p = 0.027) and more effective treatment (71.43% vs. 58.56%, p = 0.148).ConclusionsBALF mNGS identified a greater variety of pathogens than CMTs. Immunocompromised patients with suspected pneumonia may benefit more from BALF mNGS.